2012
DOI: 10.1161/circulationaha.112.124529
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Estrogen Receptor Signaling Is Essential for the Protective Effects of Estrogen Against Vascular Injury

Abstract: Background Clinical trial and epidemiological data support that the cardiovascular effects of estrogen are complex, including a mixture of both potentially beneficial and harmful effects. In animal models, estrogen protects females from vascular injury and inhibits atherosclerosis. These effects are mediated by estrogen receptors (ERs), which when bound to estrogen can bind to DNA to directly regulate transcription. ERs can also activate several cellular kinases by inducing a “rapid” non-nuclear signaling casc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 49 publications
4
87
0
Order By: Relevance
“…14,15 Multiple animal studies have demonstrated that estrogen decreases pulmonary arterial vasoconstriction by decreasing expression of endothelin 1 and increasing release of NO and prostaglandin. 8,[16][17][18][19][20] Neither of these studies addressed the effect of menopause on treatment response or evaluated time to clinical worsening (TCW) as a clinical end point.In the general population, many vasoreactive conditions, such as migraine headache and Raynaud's phenomenon, increase after menopause. 17 This postmenopausal increase is also demonstrated in PAH and is postulated to be due to estrogen withdrawal, as it has been demonstrated in animal models that lower estrogen and progesterone states produce increased pulmonary vasoconstriction.…”
mentioning
confidence: 99%
“…14,15 Multiple animal studies have demonstrated that estrogen decreases pulmonary arterial vasoconstriction by decreasing expression of endothelin 1 and increasing release of NO and prostaglandin. 8,[16][17][18][19][20] Neither of these studies addressed the effect of menopause on treatment response or evaluated time to clinical worsening (TCW) as a clinical end point.In the general population, many vasoreactive conditions, such as migraine headache and Raynaud's phenomenon, increase after menopause. 17 This postmenopausal increase is also demonstrated in PAH and is postulated to be due to estrogen withdrawal, as it has been demonstrated in animal models that lower estrogen and progesterone states produce increased pulmonary vasoconstriction.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] In vascular smooth muscle cells (SMCs), PY-STAT5b has been identified as a transcription factor which facilitates growth and motility, and neointima formation in response to thrombin, PDGF and arterial injury. [21][22][23][24][25][71][72][73][74] Suppression of activation of PY-STAT5b signaling in the vessel wall reduced balloon injury-induced neointima formation. 73 Remarkably, that hypophysectomy in the male rat markedly impaired arterial remodeling after aortic balloon injury due to reduced vascular SMC proliferation and myointima formation, was reported in 1978, 75 and confirmed, 76 but the mechanisms remained to be elucidated.…”
Section: Sex Bias and Stat5a/b In Vascular Diseasementioning
confidence: 99%
“…As examples, there is an extensive literature on the effects of E2 on increasing the function of eNOS in endothelial cells, the ability of E2 to stimulate vascular smooth muscle cell proliferation, and to inhibit the trafficking of vasorelevant receptors such as BMPR2 (bone morphogenetic receptor 2) to the cell surface. 6,[21][22][23][24][25][26][27][28] However, these studies of direct effects of sex hormones on vascular cells, taken together, have been unable to explain the many disparate sex bias observations in a vascular disease such as PH in humans and different rodent species.…”
Section: Introductionmentioning
confidence: 99%
“…7 Striatin is a member of the WD (tryptophan [W], aspartic acid [D]) repeat protein family containing a caveolin-binding domain as well as a calmodulin binding domain and serves as a molecular anchor and scaffold for assembly of proteins required for rapid estrogeninduced signaling. 8 In the study by Moens and associates in this issue of Circulation, 4 the actions of this receptor complex are defined using a novel transgenic mouse expressing a disrupting peptide consisting of the striatin-binding domain within ER␣. This peptide prevents complex formation between ER␣ and ER␤ and striatin and inhibits membrane ER signaling.…”
Section: Article See P 1993mentioning
confidence: 99%
“…To achieve this aim, new studies to better understand both nuclear and membrane estrogen receptor (ER)-mediated signaling in target tissues such as the heart and blood vessels, immune cells, and other target tissues are in progress. In this issue of Circulation, Moens and colleagues 4 provide novel insights on the importance of membrane ER-mediated signaling pathways in blood vessels for vasoprotection and vascular gene regulation.…”
mentioning
confidence: 99%